Survival Outcomes in Oral Tongue Cancer: A Mono-Institutional Experience Focusing on Age - Ansarin, Mohssen; De Berardinis, Rita; Corso, Federica; Giugliano, Gioacchino; Bruschini, Roberto; De Benedetto, Luigi; Zorzi, Stefano; Maffini, Fausto; Sovardi, Fabio; Pigni, Carolina; Scaglione, Donatella; Alterio, Daniela; et al. (Frontiers in Oncology, 2021)
OBJECTIVE The prognostic role of age among patients affected by Oral Tongue Squamous Cell Carcinoma (OTSCC) is a topic of debate. Recent cohort studies have found that patients diagnosed at 40 years of age or younger have a better prognosis. The aim of this cohort study was to clarify whether age is an independent prognostic factor and discuss heterogeneity of outcomes by stage and treatments in different age groups. METHODS We performed a study on 577 consecutive patients affected by primary tongue cancer and treated with surgery and adjuvant therapy according to stage, at European Institute of Oncology, IRCCS. Patients with age at diagnosis below 40 years totaled 109 (19%). Overall survival (OS), disease-free survival (DFS), tongue specific free survival (TSFS) and cause-specific survival (CSS) were compared by age groups. Multivariate Cox proportional hazards models were used to assess the independent role of age. RESULTS The median follow-up time was 5.01 years (range 0-18.68) years with follow-up recorded up to February 2020. After adjustment for all the significant confounding and prognostic factors, age remained independently associated with OS and DSF (respectively, p= 0.002 and p= 0.02). In CSS and TSFS curves, the role of age seems less evident (respectively, p= 0.14 and p= 0.0.37). In the advanced stage sub-group (stage III-IV), age was significantly associated with OS and CSS with almost double increased risk of dying (OS) and dying from tongue cancer (CSS) in elderly compared to younger groups (OS: HR= 2.16 95%, CI: 1.33-3.51, p= 0.001; CSS: HR= 1.76 95%, CI: 1.03-3.01, p= 0.02, respectively). In our study, young patients were more likely to be treated with intensified therapies (glossectomies type III-V and adjuvant radio-chemotherapy). Age was found as a prognostic factor, independently of other significant factors and treatment. Also the T-N tract involved by disease and neutrophil-to-lymphocyte ratio ≥ 3 were independent prognostic factors. CONCLUSIONS Young age at diagnosis is associated with a better overall survival. Fewer younger people than older people died from tongue cancer in advanced stages.